FACTORS INFLUENCING PURCHASE INTENTION OF ENERGEN PRODUCTS IN INDONESIA - Walandha, Addo Arturo; Wuisan, Dewi (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The food and beverage industry in Indonesia continues to grow, with the healthy food segment showing an upward trend. One of the well-known products in this segment is Energen. However, despite its strong branding, consumer purchase rates for Energen have declined. This study aims to identify the factors influencing the purchase intention of Energen products in Indonesia using a model that includes Health Awareness, Perceived Nutritional Content, Perceived Value, Attitude Towards Influencer, and Attitude Towards Healthy Food. A quantitative research method was employed with PLS-SEM analysis to process data from 219 respondents collected through online questionnaires. The results indicate that Perceived Nutritional Content, Perceived Value, and Attitude Towards Influencer significantly affect Purchase Intention, however Health Awareness and Attitude Towards Healthy Food do not have a significant impact on Purchase Intention. This study contributes to the academic literature on consumer behavior in the healthy food segment and provides practical implications for Energen's marketing strategies.